1996
DOI: 10.1148/radiology.200.3.8756931
|View full text |Cite
|
Sign up to set email alerts
|

Segmental anatomy of the liver under the right diaphragmatic dome: evaluation with axial CT.

Abstract: The line that extends beyond the middle or right hepatic vein from the inferior vena cava does not coincide with the main or right longitudinal scissura on axial images of the upper portion of the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 0 publications
3
19
0
1
Order By: Relevance
“…According to our results, the right and middle vertical plane angles and the S8-longitudinal angle in the S8-dominant type was more oblique and wider than in the S7-dominant type, indicating the dominant segment of the dome area of the right lobe was segment 8 in the S8-dominant type. This observation corresponded well to the findins described by Ohashi et al (10). Fasel et al (1) have described that the discrepancy of the segmental boundaries between the conventional segmentation method and the real segmental anatomy, as divided by the portal venous supply, on the axial images varied and this discrepancy was as large as 40 mm maximally.…”
Section: Discussionsupporting
confidence: 90%
“…According to our results, the right and middle vertical plane angles and the S8-longitudinal angle in the S8-dominant type was more oblique and wider than in the S7-dominant type, indicating the dominant segment of the dome area of the right lobe was segment 8 in the S8-dominant type. This observation corresponded well to the findins described by Ohashi et al (10). Fasel et al (1) have described that the discrepancy of the segmental boundaries between the conventional segmentation method and the real segmental anatomy, as divided by the portal venous supply, on the axial images varied and this discrepancy was as large as 40 mm maximally.…”
Section: Discussionsupporting
confidence: 90%
“…This model is a comprehensive topographical concept of functional liver anatomy that is easily interpretable and can be applied in most patients. However, an increasing body of evidence suggests that this concept may be an oversimplification [27][28][29][30][31]. Anatomical and radiological investigations have confirmed that the segmental boundaries, as indicated by the hepatic veins and the level of the right portal trunk, do Aberrant left and right hepatic arteries not consistently coincide with the exact location of the true portal scissurae in individual patients [28,29,31].…”
Section: Aberrant Left Hepatic Arteriesmentioning
confidence: 99%
“…In addition, Ohashi et al [18] observed discrepancies between the imaginary intersegmental boundaries and the margins of the areas actually enhanced with contrast material on axial CT arteriograms obtained with selective injections, especially in the region under the right side of the diaphragm. Lines drawn from the IVC straight through the middle or right hepatic vein did not correspond to the boundaries between the right and left lobes, which is the main (middle) longitudinal scissura, or the boundary between the anterior and posterior sectors (segments 8 and 7), which is the right longitudinal scissura (Fig.…”
Section: Limitations Of Couinaud's Conceptmentioning
confidence: 99%
“…In three-dimensional perspective with mental reconstruction from the axial images, segment 8 was revealed to overhang the right hepatic vein (Figs. 9, 10, 11, 12) [18].…”
Section: Limitations Of Couinaud's Conceptmentioning
confidence: 99%
See 1 more Smart Citation